2018
DOI: 10.1111/1744-9987.12660
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Critically Ill Patients: A Prospective Randomized Study of Tidal Peritoneal Dialysis Versus Continuous Renal Replacement Therapy

Abstract: Few studies have discussed the role of peritoneal dialysis (PD) in managing acute kidney injury (AKI) in critically ill patients. The present study compares the outcome of AKI in intensive care unit (ICU) patients randomized to treatment with tidal PD (TPD) or continuous venovenous hemodiafiltration (CVVHDF). One hundred and twenty-five ICU patients with AKI were randomly allotted to CVVHDF, (Group A, N = 62) or TPD, (group B, N = 63). Cause and severity of renal injury were assessed at the time of initiating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
110
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(117 citation statements)
references
References 37 publications
5
110
0
2
Order By: Relevance
“…The utility and efficacy of PD to treat patients with AKI was reexamined after the publication of a series of articles from Brazil, including a randomized trial, demonstrating that PD provided acceptable care and was not inferior to daily HD in treating acutely ill patients with AKI in terms of patient mortality and was associated with a shorter duration of AKI and need for renal replacement therapy 4,5 . These findings were confirmed in a randomized trial from Saudi Arabia comparing PD to hemodiafiltration 6 . AKI-PD expanded dramatically in lower resource countries with the advent of the Saving Young Lives Program in 2012 which promoted the use of PD because of minimal infrastructural requirements, including a lack of need for water or electricity, the ease of training staff, and low costs.…”
Section: Advantagesmentioning
confidence: 54%
See 1 more Smart Citation
“…The utility and efficacy of PD to treat patients with AKI was reexamined after the publication of a series of articles from Brazil, including a randomized trial, demonstrating that PD provided acceptable care and was not inferior to daily HD in treating acutely ill patients with AKI in terms of patient mortality and was associated with a shorter duration of AKI and need for renal replacement therapy 4,5 . These findings were confirmed in a randomized trial from Saudi Arabia comparing PD to hemodiafiltration 6 . AKI-PD expanded dramatically in lower resource countries with the advent of the Saving Young Lives Program in 2012 which promoted the use of PD because of minimal infrastructural requirements, including a lack of need for water or electricity, the ease of training staff, and low costs.…”
Section: Advantagesmentioning
confidence: 54%
“…In AKI-PD, the time between PD catheter placement and initial use is short and PD fluid leaks represent a complication seen with higher frequency compared to elective PD starts which usually have at least two weeks of healing time from catheter insertion to first use 22,23 . Nevertheless, the leak rates in the Brazilian and Saudi experience using high volume PD therapy immediately after catheter placement was extremely low 5,6 .…”
Section: Concerns Regarding Acute Pd and Patient Selectionmentioning
confidence: 99%
“…We had to educate ICU doctors and nurses about acute PD in AKI and the equivalence of PD to other KRT modalities, and how its use would avoid rationing. [9][10][11][12]…”
Section: Planningmentioning
confidence: 99%
“…Tidal PD was associated with better 28 day survival (70% 47%), fewer infections (10% v 18%), faster renal recovery (5 v 8 days) and shorter ICU stays (9 v 19 days). 5 A study of protein and nitrogen losses during HD (N = 40) and PD (N = 68) found greater weekly protein losses in PD (mean, 46.6 gm) than in HD (25.9 gm) but similar nitrogen losses. Notably, only about 70% of these nitrogen losses were due to losses of urea and protein suggesting that far more losses of peptides, nucleotides, organic acids and amino acids occur than is commonly believed to be the case.…”
mentioning
confidence: 98%
“…A randomized study of 125 ICU patients with AKI compared CVVHDF (30 mL/kg/h) to tidal PD (70% tidal, 24 L/d). Tidal PD was associated with better 28 day survival (70% 47%), fewer infections (10% v 18%), faster renal recovery (5 v 8 days) and shorter ICU stays (9 v 19 days) …”
mentioning
confidence: 98%